(3eSfO GdehWCs - (3YHO GdQMef Hf YHO Gddg Hf eMeO GdZGabi GdLhgQis; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s
(3ChdgG (B:s
(3CNHQfG CHh HcQ YHO Gddg Hf GdMSjf Hf YbGd GdUbdi Yf CHj gQjQI Yf GdfHi Udi Gddg Ydjg hSde bGd cd CeQ Pi HGd dGjHOC ajg HMeO Gddg agh CbWY s
(3BNQgG (B:s
(3hCOQc CQHYI ef GdUMGHI ef GdUMGHg efge hGKdI Hf GdCTaY aPdc KeGfjI hCQHYhf QLdkG ef GdJGHYjf Qhi Yfge eGdc Hf CfS ai gPG GdeSfO s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs